Influence of rates and time of Npk fertilizer application on cassava (Manihot esculenta Crantz) - Boateng, Bright Atta (2016)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology (KNUST), Kumasi, in partial fulfillment of the requirements for the award of Master of Philosophy Degree in Agronomy.